Microseismic Monitoring of Mountain Bumps and Bounces: A Case Study - J. L. Condon (International Conference on Ground Control in Mining, 1987)
The Bureau of Mines, through in-house and contract research, monitored mountain bump-prone areas of the Olga #2 Mine, near Welch, WV, using microseismic techniques for 15 months during 1985 and 1986. During this period, two ground failures occurred that were considered "mountain bumps" owing to excessive stress buildups. One failure damaged the roof and 4 pillars around an intersection; the second failure, which released much greater energy, resulted in significant damage to over 100 coal pillars. Analysis of the microseismic data collected provided significant insights into the magnitude and location of each failure. The actual failure zone was clearly delineated prior to the mountain bump occurrences through analysis of source locations of each microseismicevent. Trends in cumulative rate plots indicated the onset of structural instability. Although the data could not be analyzed automatically, the significance of the data interpretation cannot be overemphasized. Microseismic monitoring of bump-prone areas can be successful in providing a means to actually observe the structural stability occurring in underground coal mines. This paper discusses data collection techniques, analysis methods, and implications of the monitoring technique, with special emphasis on actual data from two large mountain bumps in West Virginia.